2018
DOI: 10.1177/1120672118769522
|View full text |Cite
|
Sign up to set email alerts
|

Suturing technique for scleral fixation of toric intraocular lens in the traumatic aphakic eye with corneal astigmatism

Abstract: Scleral suture fixation of foldable toric intraocular lens to correct corneal astigmatism can be a safe and effective alternative technique to manage traumatic aphakic eyes that lack adequate capsular support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…SBT technique creates free suture ends while tieing the threads on the IOL's haptics. Although it is not reported in some studies,[ 4 15 24 ] free suture ends may provoke iris chafing and inflammation by rubbing on the ciliary body and iris. Cow-hitch knots have been proposed to avoid this problem.…”
Section: Discussionmentioning
confidence: 99%
“…SBT technique creates free suture ends while tieing the threads on the IOL's haptics. Although it is not reported in some studies,[ 4 15 24 ] free suture ends may provoke iris chafing and inflammation by rubbing on the ciliary body and iris. Cow-hitch knots have been proposed to avoid this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Sutured sulcus scleral fixation of Toric IOLs are already reported as treatment for dislocated in-the-capsular-beg lens [7][8][9] as well as for recurrent intraocular lens rotation 10 ; however, the long-term stability of this technique remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al recently reported a technique using polypropylene suture to scleral fixate the haptics of a single-piece acrylic IOL without eyelets (AcrySof Toric SN6AT, Alcon, Fort Worth). 10 Because the location of fixation did not align with the steep meridian in this technique, a surgically challenging 53-degree counterclockwise rotation from the toric markings was required to achieve proper alignment in the steep corneal meridian. Conversely, the eyelet-toric IOL has marks that are in linear alignment with the eyelets to facilitate radial fixation ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%